Multi-walled carbon nanotubes covalently functionalized with polyhedral oligomeric silsesquioxanes for optical limiting - BLAU, WERNER; WANG, JUN (My University, 2010)
A soluble polyhedral oligomeric silsesquioxane (POSS) functionalized multi-walled carbon nanotube (MWCNT) hybrid material (MWCNT/POSS) was synthesized, in which the POSS content was estimated to be 44wt.%. This material exhibits a remarkable optical limiting performance for nanosecond laser pulses at 532 nm. Thermally-induced nonlinear scattering is the primary mechanism for the nonlinear optical response. This behaviour demonstrates that the MWCNT/POSS hybrid material is a suitable candidate for viable optical limiting devices
PUBLISHED
Keywords: Physics